Study on Availability of Various Macro and Micro-Minerals in Lactating Buffaloes under Field Conditions of Sabarkantha District of Gujarat - Bhanderi, B.M.; Garg, M.R.; Goswami, Ajay (Journal of Buffalo Science, 2013)
A study was conducted in the Sabarkantha district of Gujarat to assess the status of some macro and micro-minerals in lactating buffaloes. Feeds and fodder samples were collected from 17 representative villages of the district for analysis of macro and micro-minerals. Calcium content in cottonseed cake (0.17%), crushed maize (0.03%) and maize cake (0.22%) was found to be below the critical level (0.30%). The phosphorus content in concentrate ingredients was high (0.32-0.67%) but low in dry roughages (0.06-0.20%). Feeds and fodder were found to be adequate in magnesium (0.40%), sodium (0.29%) and potassium (1.15%). Straws were found to be deficient in sulphur (0.16%). Green roughages were good source of copper (12.31 ppm). Wheat straw was found to be low in zinc (19.71 ppm) but comparatively high in manganese (47.88 ppm) and iron (630.24 ppm). Lucerne and chikori green were found to be rich source of cobalt (>0.35 ppm). Selenium (0.68 ppm) was present in appreciable quantities in most of the feedstuffs. Lactating buffaloes were also found to be excess in energy and crude protein (70%), whereas, calcium and phosphorus were deficient in the ration (65%). Ration of lactating buffaloes was found to be deficient in Ca, P, S, Cu, Zn and Co. Supplementing the deficient minerals through area specific mineral mixture could alleviate the deficiency and improve productivity and reproduction efficiency of lactating buffaloes.